Studies for a horticultural building and greenhouse - Avery, Henry Albert (My University, 1902)
Introduction: The horticultural course has for its object a method of instruction and practice, as will enable the student to become acquainted with the general principles of plant culture and the application of these principles. The work is planned to give them such knowledge a will help to increase the comforts, beauties and profits of life on the farms. This course has to deal with the principles of Horticulture, Vegetable Gardening, Advanced Horticulture, Floriculture, Industrial Horticulture and several electives. In view of the fact that we have one of largest agricultural institutions in the United States, if not the world, and perhaps soon the best and most widely known of any of its kind, we are in very great need of a new horticultural building with the necessary greenhouses so have decided to write upon “Studies for a Horticultural Building” as my thesis.
Citation: Avery, Henry Albert. Studies for a horticultural building and greenhouse. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Greenhouse; Kanas State Univeristy; Buildings; Horticulture; Theses; Manuscripts (documents)